Transnational Ties: Australian Lives in the World - Deacon, Desley; Russell, Penny; Woollacott, Angela (ANU Press, 2008)
Australian lives are intricately enmeshed with the world, bound by ties of allegiance and affinity, intellect and imagination. In Transnational Ties: Australian Lives in the World, an eclectic mix of scholars-historians, literary critics, and museologists-trace the flow of people that helped shape Australia's distinctive character and the flow of ideas that connected Australians to a global community of thought. It shows how biography, and the study of life stories, can contribute greatly to our understanding of such patterns of connection and explores how transnationalism can test biography's limits as an intellectual, professional and commercial practice.